Context Association in Glaucoma Patients Using a Touch Screen. Issue 8 (August 2019) - Lenoble, Quentin; Rouland, Jean-François
Abstract : Precis: The results showed that people with glaucoma are able to perform with high accuracy a context-association task on a touch screen. This device could be a new possibility for communication and for clinical assessment. Background: The present study was designed to investigate the ability of patients with glaucoma to use a touch screen to find and associate pictures with limited text. Methods: Eighty-four volunteers were recruited in 3 groups and tested binocularly or monocularly. Twenty-eight patients with binocular glaucoma ( M =68.5 y) were selected with a visual acuity of 0.4 log MAR or better in each eye and visual field defects, with a mean deviation equal to or less than −6 dB in each eye. Twenty-eight age-matched controls ( M =68.8 y) and 28 young controls ( M =22.1 y) were also recruited (normal acuity; exclusion of ocular disease). The participants had to associate, by moving their index on a 22″ touch screen, a target on the unique scene (between 3 other distractor images) with a consistent background related to the target (eg, to match a fish with the sea). Results: The performances of the glaucomatous patients were significantly ( P <0.01) impaired in monocular vision compared with binocular vision with regard to the exploration duration (+2 s), accuracy (−3% of correct response), and peak speed (−10 cm/s). However, with binocular vision, representing daily life conditions, exploration duration, deviation, movement duration, peak speed, and accuracy were not affected by glaucoma, as demonstrated by comparison with the age-matched group. Conclusions: People with glaucoma are able to perform with high accuracy a context-association task on a touch screen. Many applications involving touch screen devices should provide new tools with limited text to help patients with visual disabilities. Abstract : Supplemental Digital Content is available in the text.